Juru Motor Sdn Bhd (Honda sales, services and spareparts) / Muhammad Hasanol Mustafa ... [et al.] - Mustafa, Muhammad Hasanol; Abdullah, Mukhtaruddin; Ali, Mohd Yassir; Mohammad Said, Sayful Hamizan; Abdullah, Khairuddin (2005)
Alter a few discussion we have decide the establishment of our business as a Honda dealers. We choose Juru Motor Sdn Bhd as our company name. Juru Motor Sdn Bhd located at 1685 Jalan Perusahaan Highway Autocity, North South Highway, Juru Interchange, 13600 perai Pulau pinang. We find this location is quite strategic because there have many competitors beside our location business, such as Proton, Chevrolet, Naza, etc. Our premise is sited in a high density business area that concludes many business types from a big asset company to a low budget business. Beside that our location is very strategic because it near the north south highway and it have many infrastructures and near to our target market. Juru Motor Sdn Bhd has five executives at directory and eighteen workers that have their responsibilities at their department. Date of our commencement is on 1st January 2006.dui ing the first year a few problems might occur because we are new in this market and our company is not well known yet. Beside that we might face a few of competitors and customers that need the lime to change their service centre from the others service centre to our service centre but some how we try to provide a good and sufficient service in order to establish our company. We believe that we will succeed although it will lake quite sometime. Furthermore our location gives advantages to run our company successfully. This is because autocity has already known as a centre of a showroom. We have decided to run our business in the form of partnership. This is because it is easier to set up a business of partnership as it only required a few formalities and risks as each of us as partners will have to share the loss. We do not have to disclose our business affairs to the public. Last of all we give fully satisfaction in our service to our customer. We hope that our business will run successfully and achieve to our target to be the number one of Honda dealers in north Malaysia.